2018
DOI: 10.1515/chem-2018-0024
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Bowel Diseases from Blood Serum by Autofluorescence and Atomic Force Microscopy Techniques

Abstract: Diagnosis of bowel diseases is often difficult and time consuming since it is not always possible to obtain adequate information by the conventional diagnostic methods to set up a diagnosis and exclude nongastrointestinal causes of symptoms. The aim of this study was to investigate the structure of blood serum samples of patients with selected intestinal diseases. The blood serum samples of patients (N=35) with selected diagnoses (mesenteric thrombosis, inflammatory bowel disease, duodenal ulcers, sepsis, ente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…We argue that patients’ sera have different protein profiles with an increased expression of some proteins involved in inflammation, and these characteristics could affect the AFM analysis, inducing a clustering of molecules on the target patches increasing the height during TNFα-infliximab recognition. This consideration could be supported by Tomeková and colleagues who have shown qualitative and quantitative changes of proteins in blood serum samples of IBD patients compared to healthy donors by fluorescence analysis and AFM technique [ 26 ]. In particular, their morphological analysis of serum deposited on a specially cleaned slide (ultrasound, special nanopaper) revealed characteristic patterns of lipids, proteins, cholesterol, and other organic compounds with significant qualitative and quantitative differences in morphology (arrangement, size, particle distribution) between the samples of healthy individuals and IBD patients.…”
Section: Discussionmentioning
confidence: 99%
“…We argue that patients’ sera have different protein profiles with an increased expression of some proteins involved in inflammation, and these characteristics could affect the AFM analysis, inducing a clustering of molecules on the target patches increasing the height during TNFα-infliximab recognition. This consideration could be supported by Tomeková and colleagues who have shown qualitative and quantitative changes of proteins in blood serum samples of IBD patients compared to healthy donors by fluorescence analysis and AFM technique [ 26 ]. In particular, their morphological analysis of serum deposited on a specially cleaned slide (ultrasound, special nanopaper) revealed characteristic patterns of lipids, proteins, cholesterol, and other organic compounds with significant qualitative and quantitative differences in morphology (arrangement, size, particle distribution) between the samples of healthy individuals and IBD patients.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in porphyrin derivatives indicative of subversion of heme metabolism was consistent with increase in the serum iron at 72 h BDL and can be used as potential intrinsic biomarkers of molecular and cellular changes in cholestasis for early diagnosis (Croce et al, 2011). There is also evidence that SFS can be used to diagnose heart ischemia (Tomečková et al, 2016) and various bowel diseases (Tomečková et al, 2018), but the relevant fluorophores in each of these studies were not identified. It is important to note that autofluorescence measurements cannot be explored as diagnostic tools simply based on their simplicity and label free approach.…”
Section: Applications Of Blood Autofluorescencementioning
confidence: 99%